Upaya Mempertahankan Hasil Belajar Matematika Siswa Kelas VIII SMP Negeri 1 Pandaan dengan Memanfaatkan Aplikasi Geogebra selama Pandemi Covid-19 Tahun Ajaran 2019/2020 - Tarsiyah, Tarsiyah (Jurnal Likhitaprajna, 2020)
The purposes of this study were to describe the learning outcomes of the grade eight students of The Pubic Junior High School I of Pandaan in mathematics in the material of flat-sided building by utilizing the GeoGebra application during the Covid-19 Pandemic situation. This type of research is Classroom Action Research. This research applied 4 lines, namely: (1) planning; (2) implementation; (3) observation; and (4) reflection. The research subjects were 35-grade eighth students of The Pubic Junior High School I of Pandaan. Data collection techniques were observation and tests. This research used 2 cycles. The analysis technique uses qualitative and quantitative data analysis techniques. The results showed that the student learning outcomes in the implementation of cycle I were the lowest score of 66 and the highest score of 90, 7 students scored below 70 minimum completeness criteria, and 28 students scored above 70 minimum completeness criteria. In other words, only 80% of students complete, and 20% of students who study do not complete their studies. While the learning outcomes in cycle II were the lowest score of 68 and the highest score of 90, 4 students scored below 70 and 31 students scored above 70. This means that only 88.6% of students completed and 11.4% of students who did not complete learn.